Halal education at the faculty of medicine and health sciences University of Muhammadiyah Makassar - Rauf, Ihsan Jaya; Aras, Dara Ugi; Bahjah, Dzata (Journal of Halal Science and Research, 2023)
The Faculty of Medicine and Health Sciences (FMHS) Universitas Muhammadiyah (Unismuh) Makassar is a medical education institution managed by Muhammadiyah, an Islamic organization in Indonesia. As an Islamic educational institution, FMHS Unismuh is mandated to develop Islamic insights in the curriculum by including teaching materials about halal in their educational curriculum, which is intended for the students. Teaching material is presented through lectures and problem-based discussions, especially on the relationship between the anatomical and physiological systems of the body. This paper aims to describe the existence of halal topics in the curriculum for students of FMHS Unismuh. The research method of this paper is descriptive analytics. This paper shows that integrated learning has implemented halal education at the FMHS Unismuh. Keywords: Halal Education, Curriculum, Integrated Learning.